THE SELECTION OF TRANSMITTERS USING FUZZY LOGIC METHOD - АЛЛАХВЕРДІЄВ, Е. Н. (Technologies and Engineering, 2023)
Problems. The main issue for solving the problem of the gas flow measurement system and its commercial accounting is to provide the metrological features required during flow measurement, as well as to create conditions for obtaining prompt, complete and reliable data. Methodology. The use of mathematical models of the devices allows to correct the indicators and dynamic characteristics of the devices, taking into account the changes in the environmental parameters. In addition to hard processing and control algorithms, one of the ways to increase the efficiency of the system is to use fuzzy processing algorithms that allow considering all possible options. Findings. The main aspects of choosing the optimal flowmeter for the data-measuring system for accounting and distribution of natural gas are considered using methods of solving multi-criteria problems under conditions of uncertainty. Effective methods of selecting a measuring device depending on technical and economic indicators of the flow meter are analyzed, taking into account the problems of determining priorities in terms of fuzziness, subjectivity of information provided by experts on flow meters of different manufacturers, warranty and service conditions. Provided by the manufacturer, problem-solving opportunities were studied, the appropriateness of using fuzzy selection methods, fuzzy algorithms, along with deterministic methods, when choosing devices that ensure the optimal output characteristics of data measurement systems, completeness and integrity of data, their output signals for processing is displayed. Originality. Effective methods of selecting a measuring device depending on technical and economic indicators of the flow meter are analyzed, taking into account the problems of determining priorities in terms of fuzziness, subjectivity of information provided by experts on flow meters of different manufacturers, warranty and service conditions. Practical value. The application of one of the methods of solving multi-criteria problems, i.e. FTOPSIS, to choose the optimal gas consumption measuring device in terms of satisfying the construction and operational characteristics presented in the development of the information measurement system, ultimately, the application of one of the methods of solving one of the alternative solutions to increase the effectiveness of the decision-making system, which opens up new opportunities in the process of choosing one of the alternative solutions can lead to simplifying (automating) the procedure of prioritizing decisions.